2017
DOI: 10.1507/endocrj.ej17-0024
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of octreotide for the treatment of congenital hyperinsulinism: a prospective, open-label clinical trial and an observational study in Japan using a nationwide registry

Abstract: Octreotide, a long-acting somatostatin analog, has been used for treating hypoglycemia caused by congenital hyperinsulinism (CHI). However, octreotide has not been evaluated in clinical trials and has not been approved in any developed country. We aimed to test the efficacy and safety of octreotide for diazoxide-unresponsive CHI through a combination of a single-arm, open-label clinical trial (SCORCH study) and an observational study to collect data on the clinical course of patients treated off-label in Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…Nevertheless, 84.0% of patients in our study maintained blood glucose > 2.8 mmol/L. The SCORCH prospective trial and observational registry study, reported by Hosokawa et al, revealed that 60% and 64.7% of patients with diazoxide‐unresponsive CHI exhibited GIR reduction > 50% at 4 weeks, respectively, the GIR was reduced by 10%–20% when fasting glucose was > 11.1 mmol/L on two consecutive occasions 15 . Our study combined blood glucose values and dextrose weaning as efficacy criteria to clarify the effectiveness of octreotide treatment.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Nevertheless, 84.0% of patients in our study maintained blood glucose > 2.8 mmol/L. The SCORCH prospective trial and observational registry study, reported by Hosokawa et al, revealed that 60% and 64.7% of patients with diazoxide‐unresponsive CHI exhibited GIR reduction > 50% at 4 weeks, respectively, the GIR was reduced by 10%–20% when fasting glucose was > 11.1 mmol/L on two consecutive occasions 15 . Our study combined blood glucose values and dextrose weaning as efficacy criteria to clarify the effectiveness of octreotide treatment.…”
Section: Discussioncontrasting
confidence: 45%
“…The SCORCH prospective trial and observational registry study, reported by Hosokawa et al, revealed that 60% and 64.7% of patients with diazoxide-unresponsive CHI exhibited GIR reduction > 50% at 4 weeks, respectively, the GIR was reduced by 10%-20% when fasting glucose was > 11.1 mmol/L on two consecutive occasions. 15 Our study combined blood glucose values and dextrose weaning as efficacy criteria to clarify the effectiveness of octreotide treatment. Demirbilek et al 10 reported that octreotide treatment was also effective in post-surgery patients who underwent near total pancreatectomy (14 patients) and focal resection (two patients).…”
Section: Efficacy Of Octreotidementioning
confidence: 99%
“…In Japan, the pre‐emptive identification of the focal form of adenosine triphosphate‐sensitive potassium channel CHI by fluorine‐18‐l‐dihydroxyphenylalanine positron emission tomography followed by local surgical resection was first reported in 2009, and has gradually become the standard management. With the progress in the diagnosis of focal CHI, more aggressive medical treatments of diazoxide‐unresponsive CHI using continuous octreotide infusion and/or enteral nutrition using gastrostomy or nasogastric feeding have also become the standard care (management flowchart available in Yorifuji et al …”
Section: Discussionmentioning
confidence: 99%
“…Thus dose adjustment may be required ( 32 , 113 , 114 ). Although various side effects have been reported in case reports, in a study evalutaing the long-term safety and efficacy of octreotide in a large series of CHI patients, it was found to be a safe and effective treatment for diazoxide unresponsive CHI patients ( 102 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ) ( Table 3 ). The effect of octreotide on linear growth have been found clinically insignificant ( 102 , 117 , 123 ).…”
Section: Introductionmentioning
confidence: 99%